Involvement of the sensorimotor cortex in physiological force and action tremor. - Marsden, J; Brown, P; Salenius, S (2001)
Whole scalp magnetoencephalography (MEG) signals were recorded in 10 healthy subjects simultaneously with the surface electromyogram (EMG) of the contralateral forearm extensor muscles during isometric contraction and phasic movement of the wrist. In eight subjects, coherence and time domain analyses demonstrated correspondence between the MEG signal, originating near or in the hand region of the motor cortex, and the 6-12 Hz EMG recorded during isometric postural contractions. In contrast, we found little evidence for correspondence between the contralateral EMG and the MEG recorded over the Rolandic region during phasic movements. We conclude that the sensorimotor cortex is differentially involved in physiological force and action tremor at the wrist.